Hubungan Pola Asuh Orang Tua Terhadap Perilaku Sosial Remaja - Kerin Ari Chaniago; Innaya Aulia Putri; Risma Anita Puriani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This article discusses the relationship between parenting styles and adolescents’ social behavior. Adolescence is a developmental stage characterized by increasing social demands, making the role of the family, particularly parents, crucial in shaping adolescents’ social adjustment. This study employed a literature review method by examining relevant textbooks and national and international journal articles related to parenting styles and adolescents’ social behavior. The findings indicate that parenting styles have a significant influence on adolescents’ social behavior. Authoritative or democratic parenting is identified as the most effective style in promoting positive social behaviors, such as empathy, cooperation, social concern, and adaptive social skills. In contrast, authoritarian and permissive parenting styles are associated with various social behavior problems, including aggression, social anxiety, and low social competence. Furthermore, the relationship between parenting styles and adolescents’ social behavior is mediated by internal psychological factors, such as self-control and emotional intelligence. Therefore, warm, responsive, and consistent parenting practices are essential to support optimal social development in adolescents.